Determinants of insecticide treated nets use among youth corp members in Edo State, Nigeria - Asagwara Chuks E; Senbanjo Idowu O; Amoran Olorunfemi E (BMC, 2011)
Abstract Background The Africa Malaria Report shows that many countries are quite far from reaching the universal coverage targets of 80% coverage by 2010 and maintain it at this level. This paper examines ITN use and the factors associated with its adoption among the youths in Nigeria. This information will help in the design of effective methods of providing and distributing the nets in order to enhance its adoption and maximize the public health benefits of ITNs. Methods This cross-sectional survey was carried out in 2006 among university leavers serving compulsory national service (youth corpers) using total sampling technique. The study was conducted using a self-administered questionnaire. Results A total of 656 youth corp members were interviewed. Only 23.8% of these youths ever use ITN while 4.3% currently use ITN before reporting in camp. A significant proportion of the youths acquired information on ITN from Mass Media (p = 0.0001). Other statistically significant factors that encourage the use of ITN include inexpensive market price of ITN (p = 0.0001), frequency of Malaria infestation (p = 0.019) and perceived malaria preventive action of ITN ( p = 0.000). Following logistic regression analysis, perceived effective malaria preventive action of ITN [OR = 29.3, C.I = 17.17-50.0] and high frequency of Malaria infestation [OR = 1.55, C.I = 0.97-2.47] were predictors of ITN use. Conclusion The study shows that the use of ITN for the prevention of Malaria is low among these Nigerian youths. The major factors determining the adoption of ITN among the youths were perceived effective Malaria prevention action of ITN and high frequency of Malaria attack. These factors should be considered in the design of sustainable and effective locally relevant strategies for scale-up adoption of ITNs among a youthful African population.